Revisión taxonómica del grupo Haplothrips-Karnyothrips(Thysanoptera: Phlaeothripidae) - P. Retana Salazar, Axel (2007)
The generic group (“ensemble”) Haplothrips-Karnyothripsis reviewed, following the most recently published criteria for distinguishing generic characters. We establish a new diagnosis for each genus. A review of a Central American collection is included and a new genus of Phlaeothripidae is described from the Central Pacific of Costa Rica from specimens collected on Cyperaceae flowers during the dry season. The genus can be distin-guished by widely separated maxillary stylets, absent maxillary bridge, pelta shape and the setae B1, which measures two thirds of the tube length. We include a key based on characters of phylogenetic importance.